Assessment of iron, folate and vitamin B12 status in children with infantile tremor syndrome - Rajpoot, Kuldeep Singh; Poswal, Lakhan; Goyal, Suresh (International Journal of Contemporary Pediatrics, 2016)
Background: Infantile tremor syndrome (ITS) is a clinical syndrome of infants and young children characterized by acute or gradual onset with mental and psychomotor changes, pigmentary disturbances of hair and skin, pallor and tremors. Methods: The study was conducted on 50 children of age group 6 – 24 months with clinical diagnosis of infantile tremor syndrome. The demographic profile and relevant information of individual patient were collected by using structured proforma and an informed consent was taken for enrolling the children into the study. Serum ferritin, folate and vitamin B12 levels were estimated to assess iron, folic acid and vitamin B12 status by electrochemiluminiscence (ECL) method. Results: Significantly higher numbers of patients (68%) were exclusively breastfed. All children had dark skin pigmentation and regression (82%)/delayed (18%) developmental milestones; while most of children had palmer pallor (98%), hypopigmented hair (92%) and majority of the patients (52%) had tremors. Significant number of patients had vitamin B12 deficiency (P=0.005) whereas none of the child was found to be having folate and ferritin deficiency. There was significant association between vitamin B12 deficiency with severity of anemia (P=0.011) and thrombocytopenia (P=0.002). Conclusions: Vitamin B12 deficiency was present in 70% of children with ITS while none of them had iron or folate deficiency.